Youth unemployment in Malaysia - Bakar, Rosni; Abdul Rahman, Shukran (2011)
The purpose of this paper is threefold. First, it will review labour force participation rate focusing on youth involvement in labour force in Malaysia. Second, it will look at the trend of youth unemployment.And thirdly, it will seek to unfold the many causes of youth unemployment with the emphasis on the graduates unemployment and graduates employability. The paper will then highlight some of the government programmes to reduce the youth unemployment especially among the university graduates.